China s new exchange rate regime, optimal basket currency and currency diversification - Zhichao Zhang; Nan Shi; Xiaoli Zhang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2011)
We build an optimising framework to analyse a class of economies that adopt an ECU-type basket currency while in transition to increased flexibility of the exchange rate regime. Instead of conventional basket pegging, such an economy uses an ECU-type currency index as a benchmark for monitoring and assessing exchange rate movements. This provides an anchoring device for the nation?s exchange rate regime and allows the home currency?s exchange rate to fluctuate. Under the assumption that the central bank is chiefly interested in maintaining stability, the optimal structure of the basket currency is based on its contribution to minimizing the volatility of the country?s external account. A currency invariance index is applied to capture the effect of the country?s exit from exclusive linkage with the US dollar. The approach is illustrated by Chinese exchange rate policy. We find it advisable and viable for China to form a basket currency with a diversified portfolio of currencies. While the portfolio?s weighting scheme could favour the dollar, euro and Japanese yen, we show that the composition of the basket is open to a wide range of possibilities. Moreover, contrary to general fears, there is considerable potential for China to engage in currency diversification, which will not necessarily affect the dollar?s position.
URN:NBN:fi:bof-201408071933
Keywords: 330